2016
DOI: 10.4088/pcc.15r01926
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery in Major Depressive Disorder

Abstract: The approach to treatment of depression that exhibits the greatest potential for achieving full symptomatic and functional recovery is early optimized treatment: early diagnosis followed by rapid individualized treatment. Monitoring symptoms and function early in treatment is crucial to ensuring that patients do not remain on ineffective or poorly tolerated treatment, which may delay recovery and heighten the risk of residual functional deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 0 publications
3
85
0
2
Order By: Relevance
“…Our results suggested that “untreated first episode” was a strong risk factor for quitting medication. This result was consistent with the current consensus of the importance of early treatment . “TCA‐treated first episode” was also a strong risk factor.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results suggested that “untreated first episode” was a strong risk factor for quitting medication. This result was consistent with the current consensus of the importance of early treatment . “TCA‐treated first episode” was also a strong risk factor.…”
Section: Discussionsupporting
confidence: 91%
“…This result was consistent with the current consensus of the importance of early treatment. 27 first episode" was also a strong risk factor. It was not difficult to understand the result, as TCAs may cause more side-effects and worse in tolerability and safety than second-generation antidepressants.…”
Section: Treatment Factorsmentioning
confidence: 94%
“…15 Importantly, analyses have shown that failure to achieve early improvement can be an even stronger predictor of a poor clinical outcome, 43,44 so that early optimization of treatment may result in faster and better outcomes (e.g., functional recovery). 15 In a previous analysis of data from desvenlafaxine trials, we found that early improvement in SDS total score at week 2 was a significant predictor of functional response or remission based on SDS total score (SDS total score ≤12 and <7, respectively), as well as combined functional/symptomatic remission (SDS total score <7 and HAM-D 17 total score ≤7) at week 8. 23 The results of the current predictor analysis further demonstrate that functional improvement at week 2 (or week 4) significantly predicts a shift in categorical measures of functioning-namely, from marked/extreme impairment (≥7) at baseline to mild/no impairment (≤3) for each SDS subscale.…”
Section: Categorical Improvement In Functionalmentioning
confidence: 99%
“…5,6 Treating MDD with urgency may be the best path to bringing patients to full functional recovery. 7,8 Although some antidepressant medications have been associated with higher remission rates than others, fewer than 50% of patients remit with any given drug. 9 In clinical practice, trials with two or more antidepressant drugs (switch or augmentation) are often needed in order to achieve remission.…”
Section: Introductionmentioning
confidence: 99%
“…8,15 Consequently, clinicians should rapidly optimize treatment in patients diagnosed with MDD to ensure that they receive adequate treatment with the least possible delay. 7,8 Clinicians can monitor patient progress using measurement-based care and adjust treatment promptly if needed. 16 Results of analyses show that improvement in depression symptoms within 2-4 weeks of starting an antidepressant predicts response and remission 7 and, importantly, that failure to show early improvement predicts poor treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%